Economic implications of unintentional carbon monoxide poisoning in the United States and the cost and benefit of CO detectors(,) - Ran, Tao (Am J Emerg Med, 2017)
BACKGROUND: Unintentional non-fire-related (UNFR) carbon monoxide (CO) poisoning has been among the leading causes of poisoning in the United States. Current estimation of its economic burden is important for an optimal allocation of resources for UNFR CO poisoning prevention. OBJECTIVE: This study was to estimate the morbidity costs of UNFR CO poisoning. We also compared the costs and benefits of installing CO detectors in residences. METHODS: We used 2010–2014 charges and cost data from Healthcare Cost and Utilization Project (HCUP), and Truven© Health MarketScan Commercial Claims and Encounters and Medicare Supplemental data. We directly measured the morbidity cost as the summation of costs for different healthcare services. Benefit of installing CO detector was estimated by summing up the avoidable morbidity cost and mortality cost (value of life). Cost of CO detectors was calculated using the average market price of CO detectors. We also calculated the benefit-to-cost ratio by dividing the benefit by its cost. All expenditures were converted into 2013 U.S. dollars. RESULTS: For UNFR CO poisoning, total annual medical cost ranged from $33.6 to $37.7 million. Annual non-health-sector costs varied from $3.7 to almost $4.4 million. The benefit-to-cost ratio can be as high as 7.2 to 1. CONCLUSION: UNFR CO poisoning causes substantial economic burden in the U.S. The benefit of using CO detectors in homes to prevent UNFR CO poisoning can considerably exceed the cost of installation. Public health programs could use these findings to promote broad installation of CO detectors in homes.